Phương trình, bất phương trình hàm số mũ và hàm số lôgarit - Phylaoud Inpanh (Đại học Đà Nẵng, 2012)
Hàm số mũ và hàm số lôgarit; Phương trình, bất phương trình hàm số mũ; Phương trình, bất phương trình hàm số lôgarit...